The Theology of Martin Luther King, Jr. and Desmond Mpilo Tutu - Hill, J. author. aut Link
XVII, 253 p.
Keywords: Hill brings two of the most prominent theologians of our time, Martin Luther King Jr. and Desmond Tutu, into conversation to explore the meaning of the Christian ideas of reconciliation, multiculturalism, and social justice for today's world. It offers a comprehensive analysis of King and Tutu's theology with implications for contemporary issues.